Handbook of Gas Sensor Materials : Properties, Advantages and Shortcomings for Applications Volume 2: New Trends and Technologies. - Korotcenkov, Ghenadii (Integrated Analytical Systems Series, 2013)
This volume offers a detailed coverage of materials for gas sensors, including the properties and relative advantages of various materials. It provides an understanding of the fundamentals of sensor functioning as well as information about applications.